Synthesis of murunskite single crystals: A bridge between cuprates and pnictides. (September 2021) - Tolj, Davor; Ivšić, Trpimir; Živković, Ivica; Semeniuk, Konstantin; Martino, Edoardo; Akrap, Ana; Reddy, Priyanka; Klebel-Knobloch, Benjamin; Lončarić, Ivor; Forró, László; Barišić, Neven; Ronnow, Henrik M.; et al.
Highlights: Murunskite interpolates between high-Tc cuprates and pnictides. First-ever large single crystals synthesized by a new reaction pathway. Sulfur ligand is structurally pnictide-like, electronically cuprate-like. Bonding band is cuprate-like, valence band pnictide-like. Numerous doping and substitution paths possible. Abstract: Numerous contemporary investigations in condensed matter physics are devoted to high temperature (high-Tc ) cuprate superconductors. Despite its unique effulgence among research subjects, the enigma of the high-Tc mechanism still persists. One way to advance its understanding is to discover and study new analogous systems. Here we begin a novel exploration of the natural mineral murunskite, K2 FeCu3 S4, as an interpolation compound between cuprates and ferropnictides, the only known high-Tc superconductors at ambient pressure. Because in-depth studies can be carried out only on single crystals, we have mastered the synthesis and growth of high quality specimens. Similar to the cuprate parent compounds, these show semiconducting behavior in resistivity and optical transmittance, and an antiferromagnetic ordering at 100 K. Spectroscopy (XPS) and calculations (DFT) concur that the sulfur 3p orbitals are partially open, making them accessible for charge manipulation, which is a prerequisite for superconductivity in analogous layered structures. DFT indicates that the valence band is more cuprate-like, while the conduction band is more pnictide-like. With appropriate doping strategies, this parent compound promises exciting future developments. Graphical Abstract: Image, graphical abstract